Effects of soluble ß-glucan on the immune responses of broiler chickens vaccinated with Newcastle disease vaccine and reared under heat stress: Nidhal Raoof Mahdi@ and Ihab Ahmed Naser - Mahdi, Nidhal Raoof (The Iraqi Journal of Veterinary Medicine, 2014)
The main objectives of this study was to determine the influence of soluble β-glucan extracted from the cell wall of Saccharomyces cerevisiae on immune response of broiler chickens reared under heat stress .β-glucan 225μg/ml was supplemented in drinking water to broiler chicken vaccinated with Newcastle disease virus (NDV) vaccine. The parameters of the assessment of the immune response was the Heterophil / Lymphocyte ratio as a measure of stress, determination of the serum antibody titer post vaccination with the NDV vaccine by ELISA test and Immunohistochemical detection of macrophages by using monoclonal antibodies (mouse antichicken macrophage KUL01). A hundred and twenty (120) Chickens one day old were divided into two equal groups; group under heat stress and group control; each group was divided into two subgroups (G1, G2, G3 and G4) containing thirty chicks. The experiment was conducted for six weeks. The stressed group exposed to heat stress (≃35ºC) starting from the third week of age upto the end of the experiment. While (Group 1) and (G3) chicks were supplemented with 225µg/ml of soluble β-glucan in drinking water from day 1 to the end of the experiment, while (G2 and G4) chicks were not supplemented. The result of Heterophil /Lymphocyte ratio indicates that there was a significant (P < 0.05) difference within heat stressed treated which showed an elevated H/L ratio at 21,28 and 35 days old. Also there was a significant (P < 0.05) difference between groups that were treated with β-glucan (G1, G3) at 21, 28 and 32 days of age compared with a control non treated non stressed group (G4) at same periods. The results of antibody titer to NDV showed that there were significant (P < 0.05) differences among all groups at 7, 14 and 21 days of age, and the results of immunohistochemical analysis demonstrated positive staining for duodenal and bursal macrophages labeled with KUL-01 mouse anti-chicken monocyte- macrophages monoclonal antibodies. Tissue sections of duodenum and bursa at 14 and 24 days old stressed and non-stressed groups treated with β-glucan showed a positive result (purple-brown staining macrophages) in G1 and G3 as compared with duodenal and bursal tissues of G2 and G4groups which showed no stained cells.